Study Of Led Lamps Technologies Impact On The Utility - Szwal, Ewelina; Puga, José Teixeira; Ferreira, Maria Judite; Gomes, António Augusto Araújo (Neutro à Terra, 2017)
With the growing interest in the issue of reducing power consumption in electricity applications, energy-saving devises and the problem of their operation gains more attention. The increase in the utilization of energy-saving lamps, especially LED lamps, leads to the wide interest in their influence on the power system. The impact of discussed devices on the voltage and current in the grid must be thoroughly studied before launching devices into the market. The studies undertaken on the LED lamps present in a wide range the issue of harmonic emission from lamps and their influence on power quality. Due to many manufacturing technologies, different LED devices can have various effects on the utility. It is significant to carry out researches concerning the adverse effects of energy-saving lamps in order to utilize devices that meet certain requirements which are set by the international commissions.